Dramas of distinction : a study of plays by golden age women - Soufas, Teresa Scott (Studies in Romance languages (Lexington, Ky.), 2015)
Renaissance Europe was the scene of flourishing and innovative dramatic art, and seventeenth-century Spain enjoyed its own Golden Age of the stage. According to traditional studies of this period, however, men seemed to be the only participants. Now in Dramas of Distinction, Teresa Scott Soufas offers the first book-length critical study of five important women playwrights: Angela de Azevedo, Ana Caro Mallen de Soto, Leonor de la Cueva y Silva, Feliciana Enriquez de Guzman, and Marfa de Zayas y Sotomayor. By locating the plays within their period, Soufas avoids universalizing women without reg.